Knowledge, Smoking Behavior, and Physical Environment’s Effect on the Pneumonia Incidence among Toddlers in Belu District - Seran, Gracia Claudia; Purnawan, Sigit; Sir, Amelya Betsalonia (Journal of Public Health for Tropical and Coastal Region, 2024)
Abstract Introduction: Pneumonia is an infectious disease caused by a virus that can affect adults and children, but is more susceptible to occur in children. This study aimed to analyze the influence of knowledge, smoking behavior, and environmental conditions on the incidence of pneumonia among toddlers in the Belu District.Methods: This research is analytic observational research using a case-control design. The total sample is 64 people categorized into 32 cases and 32 controls. The sample size was obtained using the Lemeshow formula using a comparison of 1: 1 for cases and controls. Data analysis used bivariate analysis (Chi-Square and Odd Ratio) and multivariate analysis (Logistic Regression)Results: The chi-square test results show that the significant variables are knowledge (p= 0.012, OR= 5000), smoking behavior (p= 0.001, OR= 6.600), occupancy density (p= 0.006, OR= 4.879), ventilation (p= 0.003, OR= 5.727). The results of the logistic regression test showed that the variables that had a major influence were smoking behavior (p= 0.001 OR = 10.546), and ventilation (p= 0.009 OR= 6.330).Conclusion:  The Factors affecting the incidence of pneumonia among toddlers in the Belu district are smoking behavior and home ventilation. Smoking behavior had the greatest influence on the occurrence of pneumonia based on the results of multivariate analysis.